2007
DOI: 10.1038/sj.gene.6364406
|View full text |Cite
|
Sign up to set email alerts
|

SUMO4 M55V polymorphism affects susceptibility to type I diabetes in HLA DR3- and DR4-positive Swedish patients

Abstract: SUMO4 M55V, located in IDDM5, has been a focus for debate because of its association to type I diabetes (TIDM) in Asians but not in Caucasians. The current study aims to test the significance of M55V association to TIDM in a large cohort of Swedish Caucasians, and to test whether M55V is associated in those carrying human leukocyte antigen (HLA) class II molecules. A total of 673 TIDM patients and 535 age-and sex-matched healthy controls were included in the study. PCR-RFLP was performed to identify the genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In Caucasians, the analyses of SUMO4 association with T1D produced negative results [67][68][69][70] with the exception of the dataset from North-Central Florida in the US [62,71]. In Swedish patients only, the M55 variant was not associated with diabetes by itself but increased the risk in the subset positive for the high-risk HLA-DR3/DR4 [72]. Hence, the SUMO4 M55V polymorphism seems to be specifically associated with T1D in Asians.…”
Section: Genetic Studies Revealed the Ethnic-specific Association Of mentioning
confidence: 89%
“…In Caucasians, the analyses of SUMO4 association with T1D produced negative results [67][68][69][70] with the exception of the dataset from North-Central Florida in the US [62,71]. In Swedish patients only, the M55 variant was not associated with diabetes by itself but increased the risk in the subset positive for the high-risk HLA-DR3/DR4 [72]. Hence, the SUMO4 M55V polymorphism seems to be specifically associated with T1D in Asians.…”
Section: Genetic Studies Revealed the Ethnic-specific Association Of mentioning
confidence: 89%
“…Nevertheless, as with other minor genes involved in the pathogenesis of T1D, its effect might not be significant on its own, but only through interaction with other genes, as suggested by a recent Swedish study. This work showed a positive association between the functional SUMO4 variant and T1D in highrisk HLA DR3/DR4 subjects [23].…”
Section: Discussionmentioning
confidence: 99%
“…Seven reports were excluded because they contained family data [23][24][25][26], duplicated data [9], and data not in HWE [7,27], and thus, eight reports met the inclusion criteria [3,6,8,[10][11][12][13][14]. However, one study had data on three different groups [8], and one study included five different groups [3], and we analyzed these groups independently.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 97%
“…Fifty-eight studies were identified by electronic and manual searching and 15 were selected for a full-text review based on title and abstract details [3,[6][7][8][9][10][11][12][13][14][23][24][25][26][27]. Seven reports were excluded because they contained family data [23][24][25][26], duplicated data [9], and data not in HWE [7,27], and thus, eight reports met the inclusion criteria [3,6,8,[10][11][12][13][14].…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation